Contaminant enrichment and toxicity of the Gulf's sea surface microlayer: Baseline for determining long-term persistence. (January 2022) - Fowler, Scott W.; Price, Andrew R.G.
Abstract: The Gulf contains important biodiversity, but is also heavily impacted. While studies have measured seawater contaminants and toxicity, we are not aware of discrete sampling of the sea surface microlayer (SML). This ocean-atmosphere interface is important environmentally, but also sensitive to marine and atmospheric contaminant inputs. We sampled the SML and subsurface seawater (SSW) from the Gulf in August 1991 and 1992. The SML exhibited significant enrichment of petroleum hydrocarbons, Cu, Cd and Pb, which persisted more than one year after the massive 1991 Gulf War oil spill. Toxicity to echinoderm larvae was also greater in the SML. This likely reflects effects of contaminants measured and other stressors. Sophisticated techniques used over recent decades to determine biological effects of contaminants in the Gulf could usefully extend to the SML. Our study has demonstrated its sensitivity and could serve as a 'baseline' for determining long-term persistence of seawater contamination and toxicity. Highlights: The Gulf's upper 1 mm (microlayer) was sampled separately from underlying seawater. Contaminant enrichment was evident 18 months after the huge 1991 Gulf War oil spill. Toxicity was invariably greater in the microlayer, demonstrating its sensitivity. Such unique data form a 'baseline' for assessing persistence of microlayer impacts.